Crystal structure of cesium beryllophosphate, Be3Cs2P4O14 - Fang Wang; Yigang Chen (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
Be3Cs2P4O14, orthorhombic, Pnma (no. 62), a = 15.0612(3) Å, b = 11.0386(2) Å, c = 15.5316(3) Å, V = 2582.19(8) Å3, Z = 8, Rgt(F) = 0.0229, wRref(F2) = 0.0594, T = 293(2) K.